Stroke Associated With Recent Mycoplasma Pneumoniae Infection: A Systematic Review of Clinical Features and Presumed Pathophysiological Mechanisms - Mélé, Nicolas; Turc, Guillaume (Frontiers in Neurology, 2018)
Introduction: An association between Mycoplasma pneumoniae (MP) infection and stroke has been described, especially in children. However, current knowledge on this rare potential cause of stroke is scant. The purpose of this systematic review of all published cases was to help better understand the relationships between recent MP infection and ischemic stroke on a clinical, radiological and pathophysiological perspective. Material and Methods: A PubMed and Embase search was performed in September 2018 to identify all published cases of stroke occurring within 4 weeks after MP infection. Results: Twenty-eight patients with ischemic stroke associated with MP infection were identified. Median age was 8 years (range: neonate to 57). The middle cerebral artery territory was involved in 25 (89%) patients. Fifteen (54%) patients had at least one arterial occlusion. Elevated D-dimer and/or fibrinogen was reported in 8 (29%) patients. Four patients had transient anticardiolipin IgM antibodies. Cerebrospinal fluid analysis showed pleocytosis in 7/20 (35%) patients (median: 19 leucocytes/μL, range: 10 to 63) and MP PCR was positive in 3/8 (38%) patients. The etiological work-up was considered inconclusive in 25 (89%) patients. Three (11%) patients died during follow-up, all of early respiratory deterioration. Neurological functional outcome was good in 22/27 (81%) patients. Conclusion: The association between MP infection and ischemic stroke in children and young adults is rare. Underlying pathogenesis might include hypercoagulability and vasculitis. Most patients achieve a favorable recovery. Whether MP infection could be a long-term risk factor for stroke by promoting atherosclerosis is uncertain and deserves further investigation.